Path dependencies in venture capital markets - Andrea Schertler (Kiel Institute for World Economics (IfW), 2002)
This paper examines the impact of venture capitalists' reputation building and experience accumulation on the genesis of venture capital markets. Venture capitalists must accumulate experience to successfully support high-technology enterprises. They must build reputation, i.e., a track record for successfully financing high-technology enterprises, in order to raise new funds from outside investors that have little information about the profitability of venture capital investments. Simulations are used to solve the model. The simulation results demonstrate that reputation building and experience accumulation lead to path dependencies: if venture capitalists lack experience, successive waves of unsuccessful venture-capital-backed enterprises undermine the genesis of venture capital markets.
Keywords: O41; O16; G24; 330; Reputation building; experience accumulation; dynamic efficiency; path dependencies; venture capital; Risikokapital; Unternehmensberatung; Lernprozess; Prestige; Allgemeines Gleichgewicht; Agency Theory; Theorie